(untitled) (BIRDEM Medical Journal, 2017)
Background: Guillain-Barré syndrome (GBS) is the commonest cause of acute flaccid paralysis worldwide, with an incidence of 0.6-4 per 100.000 inhabitants per year. It affects all age groups and carries an incapacity burden of up to 20%. The aims of this study were to evaluate the demographic and clinical presentation, hospital care and outcome with different modalities of treatment in adult patients suffering from GBSadmittedina tertiary care hospital in Dhaka. Methods: This observational study was done in the Neurology department of a tertiary care hospital in Dhaka.The studystarted in July-2011 and the first fiftypatients suffering from GBSwereenrolledconsecutively. Subjects included in this study were>18years of age.All the patients were interviewed and clinically examined. Relevant data were documented in a structured questionnaire. Nerve conduction Study (NCS) and Cerebrospinal fluid (CSF) study results were also documented. All of patients were watched for respiratory insufficiency and those who developed respiratory paralysis were transferred to ICU for respiratory assistance. According to clinical and electrophysiological criteria, the patients were classified into different variants of GBS. Patients were treated with intravenous immunoglobulin (IVIg), plasmapheresis, supportive care and outcome was observed. The patient who recovered and were discharged were later followed up on out patientbasis for one month Results: The commonest age group affected was 31-50 yrs with male preponderance .The mean age of study subjects was 46years. In most of the patient their weakness progressed for 3-5 days. Clinical evidence of a preceding infection was present inforty-six percent of the patientsbutcausative organism was not identified.Clinical presentations were quadriparesis in 84 % of patients, cranial nerve palsy in 48% of patients. Severe respiratory involvement requiring mechanical ventilation developed in 10% of patientsafter admission. CSF study was done and only10 subjects displayed typical findings of albumino cytological dissociation. NCS wasabnormal in all study subjects and revealed Acute Motor Sensory Axonal Neuropathy (AMSAN) in58%of study population. Among the fifty patients 23received plasmapheresis and another 9 receivedstandard IVIg therapy. Of these patients 20(88%) and 7 (77.6%) patients made significant recovery, respectively. Residual neurodeficit persisted in 6 of the remaining patients who received treatment in the form of only physiotherapy at the end of one month follow-up. Conclusion: Rapidly progressive quadriparesis with cranial nerve involvement was the commonest presentation. In this group of patients NCS proved to be a sensitive study for early diagnosis of patients with GBS in both diabetic and non-diabetic population. The axonal variety of GBS was more common than the demyelinating type. Although not statistically significant, the better response to plasmapheresis seemedencouraging. Again the patients who received IVIg or plasmapheresis early in the course of disease had faster recovery as compared to patients who received only supportive line of treatment. Birdem Med J 2017; 7(1): 38-42